Physical and mechanical properties of foamed concrete with recycled concrete aggregates - Han, Shangyu; Zhang, Peiheng; Zhang, Huihua; Kang, Dengyuan; Wang, Xianrong (Frontiers in Materials, 2023)
A large amount of waste concrete is produced during old city reconstruction. In order to realize the lightweight reuse of recycled concrete aggregate, a new preparation scheme of foamed concrete is proposed. Through single-factor tests, the effects of recycled coarse aggregate (RCA) gradation, RCA volume ratio, water-cement ratio and foam content on the preparation process and performance of RCA foamed concrete (RCAFC) were explored. The results showed that RCA grade has significant influence on the performance of RCAFC. Grading level Ⅲ (i.e., the mass ratio of five-type aggregates sized, respectively, 9.5~16 mm, 16~19 mm, 19~26.5 mm, 26.5~31.5 mm and 31.5~37.5 mm is 2:4:8:3:3) can reduce the water absorption by 4.6%, increase the compressive strength by 6.0%, and decrease the difficulty of sample preparation compared with the natural grading. The increase of RCA volume fraction is directly proportional to the compressive strength and inversely proportional to the water absorption. With the raising of water-cement ratio, the fluidity of foamed concrete paste increases linearly, the dry density decreases, the water absorption decreases first and then increases, and the compressive strength increases first and then decreases. The increase of foam content is inversely proportional to fluidity, dry density and compressive strength, and it is directly proportional to water absorption. Among the above four factors, the grade of RCA has the greatest impact on the early strength of the sample, whilst the content of foam is the smallest.